The Commodification of Female Sensuality in Indonesian Film Industry: Case Study of Warkop DKI - Debby Dwi Elsha; Andri Prasetyo Yuwono (Center for Southeast Asian Social Studies (CESASS), 2020)
This paper is an analysis of the process of commodification of female sensuality in an Indonesian- based film industry. Taking the case of Warkop DKI, a franchise film which continues commodifying comedy, social political criticism, and sexy women in generating profits since 1979. The commodification of female sensuality is displayed through stories, scenes, and shots which highlight parts of the female body as well as interactions between male and female characters that indicate sexual activities. However, in Warkop DKI Reborn: Jangkrik Boss! Part 1 and Part 2 which were released in 2017, the female sensuality was decreased. Applying qualitative method comprising from interviews, film observations and literature studies this paper found out that the presence of female producers does not play a great role in decreasing the use of female sensuality in those industry.